2021
DOI: 10.5194/isprs-archives-xlvi-4-w6-2021-303-2021
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation on Chlorophyll-a and Total Suspended Matter Concentration in Manila Bay Using Himawari-8 Ahi and Sentinel-3 Olci C2rcc

Abstract: Abstract. Water quality monitoring is important in maintaining the cleanliness and health of water bodies. It enables us to identify sources of pollutions and study trends. While modern methods include the use of satellite images to estimate water quality parameters, commonly used satellite systems, such as Landsat and Sentinel, only generate images with temporal resolution of 2 to 16 days on the average. Himawari-8 satellite system, on the other hand, generates full-disk images every 10-minutes, making it pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…MODIS is carried by satellite platforms Terra and Aqua to generate images every 1 to 2 days to observe global dynamics. Chlorophyll-a (chl-a) and total suspended matter (TSM) concentrations have been utilized to examine water quality conditions, and recent studies have shown that chl-a and TSM concentrations in Manila Bay can be determined acurately using satellites such as Himawari-8 and Sentinel-3 [6,7,8,9]. Chl-a is related to biological activity because of its correlation with nutrient concentration and algal production; and TSM indicates the presence of suspended sediments which in turn affects the amount of light that is scattered or transmitted through the water column [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MODIS is carried by satellite platforms Terra and Aqua to generate images every 1 to 2 days to observe global dynamics. Chlorophyll-a (chl-a) and total suspended matter (TSM) concentrations have been utilized to examine water quality conditions, and recent studies have shown that chl-a and TSM concentrations in Manila Bay can be determined acurately using satellites such as Himawari-8 and Sentinel-3 [6,7,8,9]. Chl-a is related to biological activity because of its correlation with nutrient concentration and algal production; and TSM indicates the presence of suspended sediments which in turn affects the amount of light that is scattered or transmitted through the water column [6].…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll-a (chl-a) and total suspended matter (TSM) concentrations have been utilized to examine water quality conditions, and recent studies have shown that chl-a and TSM concentrations in Manila Bay can be determined acurately using satellites such as Himawari-8 and Sentinel-3 [6,7,8,9]. Chl-a is related to biological activity because of its correlation with nutrient concentration and algal production; and TSM indicates the presence of suspended sediments which in turn affects the amount of light that is scattered or transmitted through the water column [6]. This study examined the spatial and temporal changes in chl-a and TSM concentrations around Manila Bay from 2002 to 2016 using MODIS images, and looked into possible factors contributing to these changes such as precipitation, run off, sea surface temperature, and wind speed.…”
Section: Introductionmentioning
confidence: 99%
“…Taniguchi et al [18] used H8 hourly sea surface temperature to describe short-term surface flow changes in the region south of the Lembeh Strait during the summer. Torres et al [19] generated annual and seasonal estimation models for Chl-a and total suspended matter (TSM) using H8 satellite data and linear regression. H8 possesses high spatial coverage and a high revisit rate [20][21][22], making it suitable for monitoring the rapid changes associated with water pollution events and meeting the dynamic monitoring requirements of remote sensing water quality inversion.…”
Section: Introductionmentioning
confidence: 99%